Modeling Of Liquefaction Potential Zone Using The Global Geospatial Model (Case Study: Special Region of Yogyakarta and Klaten Regency) - Nugraheni, Adelia Saras (Himpunan Ahli Geofisika Indonesia (HAGI), 2023)
Liquefaction is a subsequent disaster that occurred due to an earthquake. Liquefaction that occurred in the Special Region of Yogyakarta and Klaten district after the 2006 earthquake in the form of sand and clay material bursts, changes in groundwater levels and groundwater quality in community wells. The purpose of this study was to determine the potential zones of liquefaction based on global geospatial methods in the Special Region of Yogyakarta and Klaten districts. The global geospatial method models the potential for liquefaction based on the parameters Vs30, PGA, and CTI. The model was validated with groundwater depth and subsurface lithology data based on microtremor data. The validation process produces a zone of potential liquefaction in the Special Region of Yogyakarta and Klaten district. The results showed a zone with a high potential for liquefaction occurring in the southern coastal areas of Kulon Progo and Bantul. The zone is in the alluvium formation, Vs30 180 to 270 m / s, CTI 7 to 11.5, PGA 660 to 840 gal, groundwater depth 0.26 to 4.49 masl, and dominated by sand material. Zones with high potential for the occurrence of faction are also found in the fault areas of Opak Sleman and Bantul. The zone is in the formation of the younger Merapi volcano, Vs30 180 to 3.15 m/s, CTI 7 to 13.5, PGA 960 to 1140 gal, groundwater depth 0.89 to 4.7 masl, and dominated by material earth, ash, and tuff.